PENGARUH DUKUNGAN SOSIAL TERHADAP MOTIVASI DAN SCHOOL WELL BEING PADA PELAJAR DI INDONESIA - Rini Maspupah; Sherly Salsa Violina; Viyata Vira Diva; Syahnur Rahman (PSIKOWIPA (Psikologi Wijaya Putra), 2021)
Academic problems can cause any negative impact on students. An immature psychological condition sometimes also adds problems for students. If this happens for a long time, it will cause a decrease in learning motivation. This study aims to analyse the effect of social support on motivation and school well being on students in Indonesia. Social support is believed to encourage learning for students, furthermore, school well-being in students will grow because they feel their needs are met. This study uses literature review methods from several journals taken in Google Scholar and Springer. The results found that motivation and social support had a positive and significant influence on school well-being. Therefore, school well-being can be improved through increased motivation and social support.